Individual and social factors and sense of coherence in the health of the elderly in Lambayeque, 2020 - Coronel Reyes, Ivon Noemi (2022)
Objective: To determine the individual and social factors and the sense of coherence in the health of the elderly who are treated at C.S Toribia Castro Chirinos, 2020. Method: Quantitative research with a methodological design, descriptive pilot study, not experimental. The population and sample consisted of 30 older adults of both sexes, with normal cognitive status, convenience sampling was used. The technique used was the survey; For data collection, the following instruments were applied: The Barthel Index (functional assessment with Cronbach's alpha 0.92), the MINSA Socio-Family Assessment questionnaire, and the Sense of Coherence Scale (Cronbach 0.89). Main results: 73.3% of older adults studied were between 65 and 73 years old. On the other hand, it turned out that 70% were female, 96.7% of the adults According to the Socio-Family assessment: 50% of the older adults presented family risk. Regarding Sense of Coherence: the understandability and manageability dimension reached proportions greater than 73.3% and significance 83.3% non-coherent. Overall conclusion: There is a high proportion of non-coherence in the dimension of significance in older adults, it is necessary to implement health education programs from pre-old age in favor of improving coping in old age, because the significance decreases in longevity.